Entre a arena e os bastidores: da prática em desenvolvimento à práxis pedagógica do Técnico em Assuntos Educacionais no âmbito do IFRN - Coutinho, Ticiana Patrícia da Silveira Cunha (2022)
This study is about the knowledge involved in the process of the development of pedagogical practices of Educational Technicians (TAE) IFRN. It is a major reflexive synthesis on the meanings attributed by TAE on their practices and knowledge used. This research aims at comprehending the knowledge and actions involved in the processes of developing the pedagogical practice of Educational Technicians, as well as understanding the processes of knowledge production in their daily work routine. The first question is: What is the knowledge involved in the process of developing the pedagogical practice of Educational Technicians (TAE) at the Federal Institute of Education, Science and Technology in Rio Grande do Norte (IFRN)? We assume the knowledge involved in this pedagogical practice by TAE emerges from the praxis. It derives from the reflections these professionals have on their actions producing multi-referenced knowledge. Our reference unit has the information provided by 10 TAE working at different campuses at IFRN. For the accomplishment of our objectives, we adopted the comprehensive interview methodology. Our methodological principles are the multireference and the cultural and social meanings, the concepts of configuration and interdependency. Results have shown the knowledge involved in the pedagogical practice of TAE comes from: a) accumulated knowledge from their experiences; b) their working practice at IFRN, immersed in the institutional specificities and its dilemmas and challenges; and c) their reflections from their practices, that is their praxis producing multi-referenced knowledge. This knowledge is pragmatic if based on the practice or a task accomplishment. This knowledge is political if related to intentional actions and corresponds to a reflexive practice. This knowledge is hermeneutical and critical if arisen from formational processes, either collective or individual. The knowledge from TAE that emerges from their speech analysis is the outcome of the reflexive thinking on their own actions. They reflect knowledge constituted during the path of their formational process in different working spaces. They are essentially mobilized from their practices carried out at this institution.